2013
DOI: 10.1007/s10549-013-2792-7
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of endocrine treatment and outcome in the BIG 1-98 study

Abstract: Background There may be a relationship between the incidence of vasomotor and arthralgia/myalgia symptoms and treatment outcomes for postmenopausal breast cancer patients with endocrine-responsive disease who received adjuvant letrozole or tamoxifen. Patients and methods Data on patients randomized into the monotherapy arms of the BIG 1–98 clinical trial who did not have either vasomotor or arthralgia/myalgia/carpal tunnel (AMC) symptoms reported at baseline, started protocol treatment and were alive and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 39 publications
(37 reference statements)
0
27
0
Order By: Relevance
“…Recent findings support an inverse association between the reporting of early side effects under adjuvant endocrine treatment and breast cancer recurrence [3840]. Vasomotor symptoms were associated with improved disease-free and overall survival in the TEAM trial [38] and reduced breast cancer recurrence in the ATAC trial [40], but not in the BIG 1–98 [41] and MA.27 trials [42]. Thus, we cannot exclude that the CYP19A1 rs10046 (T/T) genotype might be associated with reduced exemestane + OFS efficacy: women with this polymorphism possibly lack complete estrogen suppression, despite receiving concomitant OFS.…”
Section: Discussionmentioning
confidence: 94%
“…Recent findings support an inverse association between the reporting of early side effects under adjuvant endocrine treatment and breast cancer recurrence [3840]. Vasomotor symptoms were associated with improved disease-free and overall survival in the TEAM trial [38] and reduced breast cancer recurrence in the ATAC trial [40], but not in the BIG 1–98 [41] and MA.27 trials [42]. Thus, we cannot exclude that the CYP19A1 rs10046 (T/T) genotype might be associated with reduced exemestane + OFS efficacy: women with this polymorphism possibly lack complete estrogen suppression, despite receiving concomitant OFS.…”
Section: Discussionmentioning
confidence: 94%
“…The baseline characteristics of the included studies are described in Table 1 and Supplementary Table 2 . All included studies enrolled women 18 years or older diagnosed with stage I–III breast cancer, but five studies included only postmenopausal women [ 7 8 9 10 11 ]. All studies were exploratory retrospective studies of previous phase 3 trials.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were phase 3 randomized controlled trials comparing endocrine treatment regimens, and one study was a phase 3 randomized controlled trial of the effectiveness of a high-vegetable, low-fat diet [ 5 ]. Three studies used recurrence-free survival as a primary outcome [ 5 7 11 ], whereas the others used disease-free survival as a primary outcome, including death without disease relapse as an event [ 8 9 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BIG1.98, ATAC and IES trials had previously confirmed the efficacy of aromatase inhibitors compared with tamoxifen in the adjuvant treatment of postmenopausal women in terms of risk of recurrence (range: 15-25%) and distant metastases (∼27%) [7][8][9] and increased DFS, although no significant change in the OS and a small increase in cardiovascular risk were evidenced [7]. aromatase inhibitors: management considerations Aromatase inhibitors are classified into two groups: type 1 (enzyme inactivating), with irreversible action, and type 2 (nonsteroidal, enzyme inhibitor), with reversible action.…”
mentioning
confidence: 94%